2010
DOI: 10.1080/02615470903217329
|View full text |Cite
|
Sign up to set email alerts
|

The World War Ii Patriotic Mother

Abstract: Abstract:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the little research involving parents implies that they experience military life differently than romantic partners and children of service members. For example, parents are socialized to be protectors of their sons and daughters, a role not typically occupied by spouses or children (Crow & Myers-Bowman, 2011;Garner & Slattery, 2010;Slattery & Garner, 2007, 2011. Given the critical importance of parents to the dynamics of military families, scholars have called for systematic investigation of parents' experiences of a child's military service (Andres et al, 2011;Blaisure et al, 2012;Hall, 2008;LaRossa, 2016;Polusny et al, 2014).…”
mentioning
confidence: 99%
“…However, the little research involving parents implies that they experience military life differently than romantic partners and children of service members. For example, parents are socialized to be protectors of their sons and daughters, a role not typically occupied by spouses or children (Crow & Myers-Bowman, 2011;Garner & Slattery, 2010;Slattery & Garner, 2007, 2011. Given the critical importance of parents to the dynamics of military families, scholars have called for systematic investigation of parents' experiences of a child's military service (Andres et al, 2011;Blaisure et al, 2012;Hall, 2008;LaRossa, 2016;Polusny et al, 2014).…”
mentioning
confidence: 99%
“…A study of World War II (WWII) news coverage revealed that the press helped socialize wartime mothers of soldiers by emphasizing their role as citizen and drawing on the archetype of the Patriotic Mother to reposition mothers as willing to stoically and silently sacrifice their soldier sons rather than protect them. 32 Other studies reported that while most national news accounts of the U.S. war in Iraq portrayed mothers of combat soldiers as patriotic, a small subset of stories included mothers who broke the mold by speaking to the personal cost of war and openly criticizing the government and its war policies, while also expressing support for the soldiers. These mothers were not criticized in or by the press for their antiwar positions, as they had been in the past, raising questions about a possible shift in the cultural archetype of the Patriotic Mother.…”
Section: Importance Of This Monographmentioning
confidence: 99%